1995
DOI: 10.1111/1523-1747.ep12318410
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody to cis-Urocanic Acid Prevents the Ultraviolet-Induced Changes in Langerhans Cells and Delayed Hypersensitivity Responses in Mice, Although Not Preventing Dendritic Cell Accumulation in Lymph Nodes Draining the Site of Irradiation and Contact Hypersensitivity Responses

Abstract: Ultraviolet B (UVB) irradiation of C3H mice causes suppression of delayed hypersensitivity and contact hypersensitivity (CH) to antigens encountered following exposure, and is accompanied by a reduction in Langerhans cell (LC) numbers in the epidermis, loss of epidermal antigen-presenting cell function, and accumulation of dendritic cells in lymph nodes draining the site of irradiation. Various photoreceptors and mediators of these changes have been proposed, one of which is cis-urocanic acid (cis-UCA) formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…A mAb with specificity cis-UCA was generated in BALB/c mice, as described by Norval and colleagues (24,25), and used as previously optimized. Mice were injected i.p.…”
Section: Reagentsmentioning
confidence: 99%
“…A mAb with specificity cis-UCA was generated in BALB/c mice, as described by Norval and colleagues (24,25), and used as previously optimized. Mice were injected i.p.…”
Section: Reagentsmentioning
confidence: 99%
“…It has been shown recently that the reduction in the number after topical cis-UCA or UV irradiation could be abrogated by pretreatment of the mice with a monoclonal antibody specific for cis-UCA (12). In addition this effect could be blocked by pretreating the mice with neutralizing antibodies to tumor necrosis factor-a (TNF-a), leading to the hypothesis that cis-UCA formation following UV exposure could induce TNF-a expression by keratinocytes or by Langerhans cells, which would then mediate the reduction in the numbers of Langerhans cells (13).…”
Section: Effects Of Uca In Vivomentioning
confidence: 99%
“…Antigen-specific T cells were generated in the spleens of these animals, which were capable of transferring the suppression of DH to animals already infected with HSV (17). Pretreatment of the mice with an antibody to TNF-a did not abrogate the suppression (18), while pretreatment with the cis-UCA antibody led to the complete restoration of the DH response (12).…”
Section: Effects Of Uca In Vivomentioning
confidence: 99%
“…Recently, it has been reported that C-UA has differential effects on the immunosuppression of delayed-type hypersensitivity versus CHR [19]. Antibodies to C-UA relieve UVB-induced suppression of delayed-type hypersensitivity [17] and reverse UV-induced changes in Langerhans cells but fail tu prevent CHR or accumulation of dendritic cells in the local draining lymph nodes [20]. In the experiments presented here, we sought to investigate the linkage between C-UA immunosuppression and mast cell degranulation [21].…”
Section: Introductionmentioning
confidence: 99%